The Influence of Profitabiliti, Capital Adequacy and Liquidity on Credit Management - Mubin, Burhan Aenul; Suwardi, Suwardi; Hartono, R. Djoko Setyo (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the influence of Profitability, Capital Adequacy, Liquidity on Credit Management in conventional commercial banking companies listed on the Indonesia Stock Exchange in the 2019-2022 period. The results of this research show that in particular Profitability, Capital Adequacy, Liquidity have a significant positive effect on Credit Management. Profitability has a significant negative effect on credit management. Capital adequacy has a significant positive effect on credit management. Liquidity has a significant positive effect on credit management. not examined in this research.